Design Aspects and Applications of Hybrid PV/T Solar Systems - Tripanagnostopoulos, Yiannis; Kalogirou, Soteris A. (My University, 2004)
In this paper a review of the design aspects and considerations for the hybrid Photovoltaic/Thermal (PV/T) systems is presented. In particular the systems investigated are analyzed with respect to their performance improvements, practical applications, constructional and operational requirements and environmental impact. The design concepts and the experience gained from testing PV/T prototypes with air and water heat extraction at our Universities is also included. The temperature of PV modules increases by the absorbed solar radiation that is not converted into electricity causing a decrease in their efficiency. This undesirable effect can be partially avoided by heat extraction with a fluid circulation. In hybrid PV/T solar systems the reduction of PV module temperature can be combined with a useful fluid heating. Therefore, hybrid PV/T systems can simultaneously provide electrical and thermal energy, thus achieving a higher energy conversion rate of the absorbed solar radiation. These systems consist of PV modules coupled to heat extraction devices, in which air or water of lower temperature than that of PV modules is heated whilst at the same time the PV module temperature is reduced. In PV/T system applications the production of electricity is the main priority, therefore it is necessary to operate the PV modules at low temperature in order to keep PV cell electrical efficiency at a sufficient level. This requirement limits the effective operation range of the PV/T thermal unit for low temperatures applications such as space heating and natural ventilation of buildings, and air or water preheating. In PV/T systems the thermal unit for air or water heat extraction, the fan or pump and the external ducts or pipes for fluid circulation constitute the complete system.
Keywords: Performance; Photovoltaic/Thermal (PV/T) systems